2022
DOI: 10.1530/etj-22-0047
|View full text |Cite
|
Sign up to set email alerts
|

TPO antibody status prior to first radioactive iodine therapy as a predictive parameter for hypothyroidism in Graves’ disease

Abstract: Objective We investigated if a positive thyroid peroxidase antibody (TPO Ab) status before radioactive iodine (RAI) therapy in patients with Graves’ hyperthyroidism is a predictive factor for developing hypothyroidism post RAI. Methods We performed a retrospective study of patients with Graves’ hyperthyroidism with known TPO Ab status, receiving a first administration of RAI. Patients from 4 thyroid outpatient centres in Belgium receiving a first RAI therapy between the years 2011 and 2019 were studied. Clini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 24 publications
2
8
0
Order By: Relevance
“…In most cases, TPO-Ab was tested to evaluate the incidence of Hashimoto's thyroiditis after I-131 ablation. 55,56 In this study, the slight elevation of TPO-Ab might be attributed to the increasing apoptosis of thyroid cancer cells and the subsequent release of TPO into circulation due to I-131 damage.…”
mentioning
confidence: 64%
“…In most cases, TPO-Ab was tested to evaluate the incidence of Hashimoto's thyroiditis after I-131 ablation. 55,56 In this study, the slight elevation of TPO-Ab might be attributed to the increasing apoptosis of thyroid cancer cells and the subsequent release of TPO into circulation due to I-131 damage.…”
mentioning
confidence: 64%
“…38 Autoimmune thyroid disease, hypothyroid, and euthyroid patients have a high prevalence of TPO-Abs, and their measurement is helpful in the diagnostic workup of these patients. 38 Yet, Khoo et al 39 demonstrated that the absence of thyroid peroxidase antibodies together with high TSI levels in Graves disease identifies a group at a markedly increased risk of ophthalmopathy. Recent studies have proved the therapeutic effect of selenium in TED and it is believed that selenium reduces the TSHR-Ab and TPO-Abs in addition to an inhibitory effect of HLA-DR molecule expression on thyrocytes, prevention of dysregulation of cell-mediated immunity and B-cell function, neutralizing reactive oxygen species, and inhibition of expression of proinflammatory cytokines, prostaglandin, and leukotriene synthesis.…”
Section: Tbiimentioning
confidence: 99%
“…Also, 10% to 15% of normal individuals can have high levels of TPO-Ab titers 8,37 . TPO is expressed in orbital tissues, and the polymorphism rs11675434 SNP has been proven to be associated with clinically evident TED 38 . Studies in pediatric patients have also shown a positive correlation between high TPO-Ab levels and TED 38 .…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations